Islamic Republic of Afghanistan : Afghanistan National Development Strategy; First Annual Report (2008/09). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the First Annual Report (2008/09) on the Afghanistan National Development Strategy (ANDS). The economic and security situation was particularly challenging during the first year of ANDS implementation (1387 or 2008/09) owing to rapid increases in food and fuel prices and sharply increased violence in some provinces. Both imports and exports have been increasing at high rates. A major concern continues to be slow progress in meeting revenue targets and the ability to effectively control spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet